Inclusive Classroom Strategies: Enhancing Learning Outcomes for Students with Autism Spectrum Disorder - Shazia Afzal (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The goal of inclusive education is to make learning spaces fair for all students, no matter how smart they are. Students with Autism Spectrum Disorder (ASD) may have distinct obstacles in conventional classes, such as issues with communication, social engagement, and sensory control. This research examines evidence-based inclusive classroom techniques that improve the educational results of kids with ASD. Some of the most important methods include differentiated instruction, visual aids, peer-mediated learning, sensory-friendly changes, and the use of assistive technology. The report stresses how important it is for teachers to be ready, get individual help, and work together to plan. The study discusses the problems that make it hard to include everyone, such not having enough resources or teachers who aren't trained well enough. It also gives useful advice to teachers and legislators. The results show that with the correct tactics and support structures, inclusive classrooms may help kids with ASD do better in school, get along with others, and feel better emotionally.